Honeypot in the Cyber Space - Astha, Mk; Verma, Anany; Rana, Sadhna; Singh, Himanshi (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In today’s world a large number of devices are connected to the network, which indicates that there could exist more access nodes than before from where an intruder can try to attack and gain access to the network and its connected devices. As technology is evolving rapidly it’s difficult to keep pace with the latest trends in cyber space. The already existing defense mechanisms that have been used traditionally are falling behind to keep pace with the evolutions in the field of cyber security. In the recent times every device we own is somehow connected to the network. Thus, a greater number of cyber threats are evolving rapidly and the traditional mechanisms are not at par with the current trends like firewalls, (IDS) intrusion detection system and (IPS)intrusion prevention system. This paper presents a comprehensive study on the life cycle of honeypot systems, emphasizing planning, deployment, operation, data collection, analysis, maintenance, and evolution phases. It also discusses the different types of honeypots based on interaction levels and deployment methods, highlighting inherent challenges and considerations in modern cybersecurity infrastructures. This paper throws light on the life cycle of a honeypot and its implementation as a telnet honeypot. That is used to record any unauthorized login attempts and create log files that can be used for further analysis about the attacks performed on the honeypot. The honeypot shows a telnet vulnerability that could be used for remote login which can be easily found by an intruder and not to the public. Further the honeypot records the activity, attacks and more in the form of logs.